Recent advances in in situ Notch signaling measurement - Yoshihara, Masaharu; Takahashi, Satoru (Frontiers in Cell and Developmental Biology, 2023)
Notch signaling is necessary for the development of many organ systems, including the nervous system, biliary system, and visual and auditory sensory systems. This signaling pathway is composed of DSL ligands and Notch receptors. Upon the interaction of those components between neighboring cells, the intracellular domain of the Notch receptor is cleaved from the cell membrane to act as a transcription factor. To date, many mechanistic insights, including lateral inhibition and lateral induction, have been proposed from observation of patterning morphogenesis and expression profiles of Notch signaling-associated molecules. The lack of a direct measurement method for Notch signaling, however, has impeded the examination of those mechanistic insights. In this mini-review, recent advances in the direct measurement of Notch signaling are introduced with a focus on the application of genetic modification of Notch receptors with the components of the Cre/loxP system and Gal4/UAS system. The combination of such conventional genetic techniques is opening a new era in Notch signaling biology by direct visualization of Notch "signaling" in addition to Notch signaling-associated molecules.